2000
DOI: 10.1021/bi991982r
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Citrate Synthase from the Thermophilic Archaeon Thermoplasma acidophilum

Abstract: The kinetics and mechanism of the citrate synthase from a moderate thermophile, Thermoplasma acidophilum (TpCS), are compared with those of the citrate synthase from a mesophile, pig heart (PCS). All discrete steps in the mechanistic sequence of PCS can be identified in TpCS. The catalytic strategies identified in PCS, destabilization of the oxaloacetate substrate carbonyl and stabilization of the reactive species, acetyl-CoA enolate, are present in TpCS. Conformational changes, which allow the enzyme to effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(69 citation statements)
references
References 67 publications
5
64
0
Order By: Relevance
“…In a recent study of citrate synthase (CS), protein flexibility during catalysis was found to be a major determinant in the rate of catalysis. 33 CS performs a Claisen condensation between oxaloacetate and actetyl-coenzyme A to form citrate and coenzyme A. When CS from a moderate thermophile was compared to a mammalian CS, it was found to be significantly more rigid, probably in order to cope with the higher temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of citrate synthase (CS), protein flexibility during catalysis was found to be a major determinant in the rate of catalysis. 33 CS performs a Claisen condensation between oxaloacetate and actetyl-coenzyme A to form citrate and coenzyme A. When CS from a moderate thermophile was compared to a mammalian CS, it was found to be significantly more rigid, probably in order to cope with the higher temperature.…”
Section: Discussionmentioning
confidence: 99%
“…18,34,35 On the basis of the analysis of CS, one would expect that the extensive flexibility in KDO8PS would result in a significant rate of reversibility. 33 The E. coli KDO8PS avoids this problem by two methods. A major conformational change, the closing of L7, occurs only as result of PEP binding followed by A5P binding, in the correct orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structures of CS have been determined and compared for organisms capable of growth over a very wide range of temperatures, from the Antarctic bacterium Arthrobacter sp. strain DS2-3R (maximum growth at 30°C) (42), mesophilic organisms such as chicken and porcine heart (37°C), thermotolerant organisms such as Thermoplasma acidophilum (55°C) (28), and the extreme thermophiles Sulfolobus solfataricus (88°C) (8), and Pyrococcus furiosus (100°C) (28).…”
Section: Discussionmentioning
confidence: 99%
“…Dethiaacetyl-CoA was prepared as described (21). The Tp CS-expressing pRec7-ArCS plasmid (3) was mutated with a QuikChange kit (Stratagene) and oligodeoxynucleotides (Supporting information, Table S1) from IDT to furnish plasmids pJK381 (D317G– Tp CS) and pJK382 (D317N– Tp CS). For experiments in D 2 O solutions, the pD was calculated from the pH meter reading (calibrated with standards in H 2 O) by adding 0.4 (22).…”
Section: Methodsmentioning
confidence: 99%